Key figures on Europe 2012 (Luxembourg, 2012)
"Key figures on Europe presents a selection of statistical data on Europe. Most data cover the European Union and its Member States, while some indicators are provided for other countries, such as members of EFTA, candidate countries to the European Union, Japan or the United States. The pocketbook treats the following areas: economy and finance; population; health; education and training; the labour market; living conditions and social protection; industry, trade and services; agriculture, forestry and fisheries; international trade; transport; the environment; energy; and science and technology. This pocketbook, which presents a subset of the most popular information found in Europe in figures – Eurostat yearbook 2011, may be viewed as an introduction to European statistics and provides guidance to the vast range of data freely available from the Eurostat website. "